Experimental substantiation of effectively administration of vinboron for analgesic activity increase of ibuprofen - F. V. Hladkykh; N. H. Stepaniuk (Zaporozhye State Medical University, 2016)
Background. The increase of NSAIDs safety is current direction of modern pharmacology, because of so-called "class-specific" adverse reactions, which are common to this class, and the leading place among them is occupied by gastro-intestinal toxicity. In previous studies we have proved the ability of vinboron to neutralize ulcerogenic effect of ibuprofen (Hladkykh F.V. and al., 2014). The presence of the proven analgesic activity in the domestic antispasmodics (Stepaniuk H.I. and al., 2007) serves as the basis for research of vinboron action on analgesic aspect of ibuprofen pharmacotherapeutic effec. Aim is to conduct research in silico of the relation «molecular structure - anelgetic activity» of vinboron and to prove experimentally in vivo the practicability of vinboron using with the aim to increase the analgesic activity of ibuprofen on the model of adjuvant arthritis in rats. Materials and methods. The study of the relation «molecular structure - activity anelgetic» of vinboron was conducted in silico by PASS- analysis of biological activity spectrum. The analysis was set online with direct insertion of structural formula of vinboron in browser using Marvin JS web-resource «PASS Online» (http://www.way2drug.com/passonline). Analgesic activity in vivo was studied on the model of acute thermal pain, which was simulated in the conventional behavioral test of nociception «Hot plate». The lag of pain reaction was determined at the beginning («0» day), on 7, 14, 21 and 28 days of experiment. Results and discussion. According to the PASS-forecast the mechanisms of vinboron analgesic activity is caused by agonism towards the vanilloid (TRPV1) receptors (Pa=0,490; Pi=0,008), agonism to the μ (mu) - receptor (Pa=0,323; Pi=0,036), inhibition of GABA (Pa=0,329; Pi=0,089) and others. Experimental studies have shown that the combined administration of ibuprofen and vinboron analgesic activity was higher than the results by ibuprofen monotherapy at a dose of 73 mg/kg up by 15.3%, and at a dose of 218 mg/kg up by 20.4%. Besides, it is worthwhile to note that analgesic activity during the integrated administration of ibuprofen at a dose of 218 mg/kg and vinboron (+39.8%) was higher than the total analgesic activity of ibuprofen monotherapy at the same dose (+19.4%) and monotherapy of vinboron (+10.9%), that points at potentiation of analgesic effect of both drugs during their integrated administration. Conclusions. According to the PASS-analysis, the leading mechanism in analgesic component implementation of vinboron is its agonism to TRPV1. The results of our in vivo studies point at the ability of vinboron to intensify the antinociceptive activity of ibuprofen.